The top nations in the medal table of the current olympic games - Shvetsov A.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determine the ranking of teams in the medal table and the contribution of athlete training systems in Olympic sports among the nations that have achieved the most success in the modern Olympic Games. Methods and structure of the study. The final results of the competitions and the information from specialized literature on the history and statistics of the modern Olympic Games are being examined and summarized. Results and conclusions. It has been confirmed that one of the key factors for the success of nations in the modern Olympic Games, as seen by fans, athletes, politicians, and the media, is the nation's position in the Olympic medal table. At present, a group of 16 nations has emerged as the top contenders in the Olympic medal table, having secured at least 100 gold medals at the Olympic Games. The United States, the Soviet Union, and China currently lead the Olympic medal table. Among the nations with the most developed state-sponsored athlete training systems, China (ranked third) and Russia (ranked 13th) stand out. The achievements of the other top nations in the Olympic medal table also demonstrate the significant influence of the state in fostering athletes in Olympic sports.